Back pain and radicular pain after lumbar microdiscectomy - Koivunen, Konsta (My University, 2023)
Purpose: It is generally expected that lumbar microdiscectomy affects radicular leg pain, but not so much local back pain. The primary objective was to evaluate if the trajectories of changes in pain severity follow similar patterns for back and radicular leg pain after lumbar microdiscectomy. The secondary objective was to investigate the associations between some preoperative parameters and the patterns of these trajectories. Methods: Register-based retrospective study of 353 patients undergoing microdiscectomy in the lumbar spine. Linear mixed modelling was applied. Results: The average age of the participants was 46 years and 44% were women. The developmental trajectories were similar for both back and leg pain. Pain level decrease during the first year after the surgery, slightly worsening later. No statistically significant interactions were detected of preoperative pain duration or severity, sex or age on the shapes of the trajectories. For every analyzed grouping factor, the 95% confidence intervals overlapped at every postoperative time point with one exception – worse preoperative back pain was statistically significantly associated with worse pain at three months and at the end of the two-year follow-up. Conclusion: After microsurgical discectomy, developmental curves for both back and radicular leg pain demonstrated similar patterns. Pain intensity decreased during the first year after the surgery. and slightly increased after that remaining, however, below the preoperative level. Age, sex, preoperative pain duration or preoperative intensity of leg pain were not associated with significant differences in the trajectories of pain severity after the surgery. In this study, severe preoperative back pain was the only factor, which was significantly associated with worse postoperative trajectory of pain intensity.
Keywords: Diskectomy, Microsurgery, Low Back Pain, Musculoskeletal Pain, Pain Management